Political leaders' experiences of local council, board and committee work and its challenges in Finland - Minna Joensuu; Vuokko Niiranen (Administrative Sciences, 2019)
The relationship between political leaders and public administrators is a layered and multi-dimensional phenomenon influenced by both organizational characteristics and personal qualities and skills. Continuous reforms of local government structures lead to changes in the interaction between these key actors. The purpose of this article is to investigate if different interaction patterns of political leaders influence how they perceive their duties as political leaders. The empirical data was collected by a questionnaire from political leaders in six local government organizations in Finland. The political leaders were then grouped into three using factor analysis and k-means clustering according to their interaction styles in their positions in the strategic level decision-making. The further analysis utilized contingency tables. The results suggest that the three groups among the political leaders think and act in different ways. The differences are not based on political opinions, but on attitudes towards the decision-making process and the political leaders' modus operandi. There are also differences what the political leaders find most difficult in their duties. These groups form one more layer in modern local government decision-making. Recognizing the different patterns of interaction may help us to better understand the dynamics of strategic management in the local government.
Keywords: 350; local government; municipalities; political leaders; public administrators; decision-making; strategic management